E-Learning: Inovasi Media Pembelajaran di Era Digital - Wati, Erlina Eka; Husnia, Masna Binta Aida; Anbiya, Bakti Fatwa (Jurnal Al Burhan, 2024)
This study aims to explain the concept of E-Learning in general as a learning medium in the digital era which includes: 1) definition; 2) characteristics and benefits; 3) advantages, disadvantages, constraints and effectiveness of application; 4) analysis and development design; 5) the function of the e-learning system; 6) development of "Search Engines"; and 7) learning sites or e-learning websites. The method used in this study is a descriptive qualitative method through a literature study approach. Data is collected through various relevant literacy sources such as books, articles, journals, and others. This study shows the importance of appropriate learning media to help achieve learning objectives. This study is expected to add insight for readers related to one of the learning media innovations in the digital era, namely e-learning. This study has implications in the field of education, especially in improving the efficiency and effectiveness of learning. Through e-learning one can access a wider range of knowledge that can help in the learning process.